An experimental study of moisture buffering of bio-insulations in lofts. Issue 5 (4th November 2014) - Tucker, Simon; Latif, Eshrar; C. Wijeyesekera, Devapriya
Abstract : Purpose: – The purpose of this paper is to describe and discuss initial work to assess the moisture buffering performance of selected bio-insulations in lofts that suffer from excessive moisture following refurbishment. Design/methodology/approach: – These conditions were then reproduced in a physical lab-based experiment such that the comparative performance of the bio-insulations and stone wool could be measured. Findings: – It was found that the bio-insulations could remove over 60 per cent of the moisture in the loft air, and therefore reduce the risk of condensation and its severity. Research limitations/implications: – The initial work reported here is indicative of the buffering potential of bio-insulations but further work is required to better quantify this performance. There is a need to further examine lofts with moisture problems and to produce reliable testing methods and protocols to be used when retrofitting loft insulation. Practical implications: – Installers and specifiers of loft insulation should ensure that insulation is installed correctly, as with the drive to increase loft insulation levels the risks of damaging the building fabric through condensation are increasing. Social implications: – Excessive moisture can damage the building fabric and create health problems. Using insulations that perform well across a range of performance criteria tend to favour bio-insulations, which have a far less harmful impact on the environment than do typical fossil-fuel based insulations. Originality/value: – The paper presents preliminary findings that support arguments for specifying bio-insulations.